Praktik Money Politik Pada Pilkada Di Kabupaten Aceh Singkil Tahun 2017 (Studi Analisis Praktik Money Politik Kecamatan Simpang Kanan) - Asmi dar; Dr. Effendi Hasan, M.A. (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2019)
Pilkada di Kabupaten Aceh Singkil tahun 2017 studi analisis Kecamatan Simpang Kanan semua calon Bupati dan Wakil Bupati melakukan pelanggaran pidana terkait money politik, diantaranya: 1.) Penyebab terjadinya money politik pada pilkada di Kabupaten Aceh Singkil tahun 2017: a, kurangnya keterbukaan informasi mengenai praktek money politik. b, tingginya angka kemiskinan di Aceh Singkil yang sudah mencapai 22,11% selama dua tahun terakhir. c, korupsi yang tiada henti setiap waktunya dan berbagai macam bentuk dikalangan penguasa, birokrasi bahkan pemerintahan, d, rendahnya kualitas Sumber Daya Manusia (SDM). Kualitas SDM merupakan komponen penting dalam setiap gerak pembangunan. e, lambatnya pembangunan infrastruktur yaitu salah satu penghambat perekonomian saat ini. Hal ini jelas bahwa kurangnya kualitas dan kuantitas infrastruktur atau prasarana. Sehingga dapat dilihat memiliki kesulitan bagi masyarakat. f, perhatian pendidikan pemerintah masih sangat minim. Hal ini jelas bahwa beragam masalah pendidikan yang makin rumit, kualitas siswa masih rendah, pengajar kurang profesional, biaya pendidikan yang mahal. Pendidikan mempunyai peran penting dlam menyiapkan sumber daya manusia untuk pembangunan. 2.) Upaya KIP mencegah money politik pada pilkada di Kabupaten Aceh Singkil Tahun 2017 yaitu: a, dengan cara melakukan sosialiasi larangan/pencegahan praktek money politik. b, memberikan pengertian money politik kepada masyarakat. c, melakukan pengawasan setiap saat pelaksanaan pilkada tujuannya untuk mengurangi adanya praktek money politik.Kata Kunci: KIP, Upaya, penyebab terjadi, mencegah, Money PolitikThe Practice of MoneyPoliticsin 2017 elections of Aceh Singkil Regency(Analysis Study of Simpang Kanan District)ABSTRACT The 2017 elections in Aceh Singkil Regency in an analysisstudy of Simpang Kanan District showed that all the candidates of Regent and Vice Regent had comitted criminal offense related to money politics, including: 1.) Causing the existence of money politics in 2017 elections in Aceh Singkil Regency: First, the lack of transparency of information about the practice of money politics. Second, the high number of poverty in Aceh Singkil had reached 22,11% over the last two years. Third, corruption was always relentless and came with a wide variety of forms among the rulers, the bureaucracy and even the government. Fourth, the low quality of Human Resources (HR). The quality of human resources was an important component in every motion of development. Fifth, the slow pace of infrastructure development, which was one of the obstacles in today's economy. It clearly showed that they lack the quality and quantity of infrastructures. So this can cause difficulty for the community. Sixth, the  government's attention towards education was still very minimal. It was clear that the diverse educational problems were more complicated, the quality of students was still low, teachers were less professional, and the cost of education was expensive. Education has an important role in preparing human resources for development. 2.) The efforts of KIP to prevent money politics in the 2017 elections in Aceh Singkil Regency, namely: First, by way of socializing the prohibition/prevention of the practice of money politics. Second, providing an understanding of political money to the community. Third, performing constant surveillance at any conducted time of the elections with the goal was to reduce the practice of money politics.Keywords: KIP, Efforts, cause of occurence,preventing,money politics